Pelatihan Microsoft Word dan Excel dengan model teaching clinic untuk meningkatkan kompetensi guru SD Negeri 106155 Tandem Hilir, Deli Serdang - Roberto Kaban; Tri Indah Prasasti; Siti Jamilah Br Tarigan; Aidatul Amelia; Putri Ramadhani Br. Sembiring; Taufik Regiwista Ramadhani; M. Rizky Syahputra Pardede (Universitas Sanata Dharma, 2026)
This community service activity aimed to improve teachers’ competence in utilizing Microsoft Office applications, particularly the mail merge feature in Microsoft Word and basic formulas in Microsoft Excel, to support school administrative tasks such as student data management and grade calculation. The activity involved 12 teachers at SD Negeri 106155 Tandem Hilir, Deli Serdang. The training applied a teaching clinic approach, which emphasizes hands-on practice, guided exercises, individual mentoring, and discussion to help participants solve practical administrative problems. The program was implemented in two training sessions within two weeks. Evaluation was conducted using questionnaires to measure participants’ perceptions of training effectiveness, relevance, materials, and delivery. The results showed positive outcomes. In the first session, 85.8% of participants rated the mail merge training as efficient, 89.2% considered it relevant to teachers’ activities, and 91.2% rated the training delivery as very good. In the second session, 96.4% of participants stated that the Microsoft Excel formula training was beneficial, while 95.5% rated the training performance and facilities as very good. These results indicate that the teaching clinic approach effectively improves teachers’ competence in using Microsoft Office for school administration